Data for: Wolverine density distribution reflects past persecution and current management in Scandinavia ... - Moqanaki, Ehsan; Milleret, Cyril; Dupont, Pierre; Brøseth, Henrik; Bischof, Richard (Zenodo, 2023)
After centuries of intense persecution, several large carnivore species in Europe and North America have experienced a rebound. Today's spatial configuration of large carnivore populations has likely arisen from the interplay between their ecological traits and current environmental conditions, but also from their history of persecution and protection. Yet, due to the challenge of studying population-level phenomena, we are rarely able to disentangle and quantify the influence of past and present factors driving the spatial distribution and density of these controversial species. Using spatial capture-recapture models and a data set of 742 genetically identified wolverines Gulo gulo collected over ½ million km 2 across their entire range in Norway and Sweden, we identify landscape-level factors explaining the current population density of wolverines in the Scandinavian Peninsula. Distance from the relict range along the Swedish-Norwegian border, where the wolverine population survived a long history of ... : This dataset is extracted from the database Rovbase 3.0 at www.rovbase.no or www.rovbase.se. Please read the README file. The data and R scripts of the spatial capture-recapture analysis are also available at: https://github. com/eMoqanaki/WolverineDensitySCRFunding provided by: Norges Forskningsråd Crossref Funder Registry ID: http://dx.doi.org/10.13039/501100005416 Award Number: NFR 286886Funding provided by: Naturvårdsverket Crossref Funder Registry ID: http://dx.doi.org/10.13039/501100004357 Award Number: Funding provided by: Miljødirektoratet Crossref Funder Registry ID: http://dx.doi.org/10.13039/501100008776 Award Number: Funding provided by: Norges Miljø- og Biovitenskapelige Universitet Crossref Funder Registry ID: http://dx.doi.org/10.13039/501100008119 Award Number: ...